Stage costume and problems of theatrical symbolism in Ukraine: Based on the premiere performance of drama “stone host” by Lesya Ukrainka in 1914 - Nesen, Iryna (Linguistics and Culture Review, 2021)
Theater as a form of cognition of the phenomenon of man and society is of interest to researchers in various fields. This is a consequence of the syncretism of all the elements that shape the art of theater. An important place in the art of theater is a costume, according to modern theater critic Patrice Pavi, as one of the main elements of the organization of stage space, which directly affects the integrity of the scenery and its integration with the actor’s body. They open the image of each character: by determining the age, sex, character, profession, emphasize individuality or typify the person. The costume is a sign of a person and at the same time a means that allows reincarnation into another person. With the help of staging, the principle of the inner composition of the play is determined: the interaction of the costumes with each other in terms of cut, shape, color, material and place in the overall scenography of the design. The problems of costume in the system of Ukrainian theater remain little studied, in contrast to folk costumes or the history of fashion.